Toxicological Evaluation of a Mixture of Astragalus membranaceus and Panax notoginseng Root Extracts (InnoSlim®). (1st July 2019) - Murbach, Timothy S.; Glávits, Róbert; Endres, John R.; Hirka, Gábor; Vértesi, Adél; Béres, Erzsébet; Szakonyiné, Ilona Pasics
Abstract : Astragalus spp. and Panax spp. have a long history of traditional human use. A blend, InnoSlim®, of highly purified and fractionated root extracts from Astragalus membranaceus and Panax notoginseng has now been developed for human consumption; however, the unique constituent content of this blend has not been specifically evaluated with respect to safety. Therefore, the toxicological potential of the blend was formally investigated in a series of studies—genetic toxicity was evaluated in a bacterial reverse mutation test followed by an in vivo mammalian micronucleus test, and general toxicity was evaluated in a 28-day repeated-dose oral toxicity study in rats. No evidence of mutagenicity was observed in the bacterial tester strains used, and no evidence of in vivo chromosomal damage resulting in increased frequency of micronucleated cells was observed in male Crl:NMRI BR mice. No mortality or toxic effects were observed, and no target organs were identified, in male and female Han:WIST rats exposed to 0, 400, 800, or 1200 mg/kg bw/day of the blend by gavage for 28 consecutive days. The highest dose—1200 mg/kg bw/day—was determined to be the NOAEL. Based on these results, extrapolation towards a safe human consumption level can be explored.